Activation of odorant receptor in colorectal cancer cells leads to inhibition of cell proliferation and apoptosis - Weber, Lea (PLoS One, 2017)
The analysis and functional characterization of ectopically expressed human olfactory receptors (ORs) is becoming increasingly important, as many ORs have been identified in several healthy and cancerous tissues. OR activation has been demonstrated to have influence on cancer cell growth and progression. Here, ORs were identified using RNA-Seq analyses and RT-PCR. We demonstrated the OR protein localization in HCT116 cells using immunocytochemistry (IHC). In order to analyze the physiological role of OR51B4, we deorphanized the receptor by the use of CRE-Luciferase assays, conducted calcium imaging experiments as well as scratch- and proliferation assays. Furthermore, western blot analyses revealed the involvement of different protein kinases in the ligand-dependent signaling pathway. Receptor knockdown via shRNA was used to analyze the involvement of OR51B4. We identified OR51B4, which is highly expressed in the colon cancer cell line HCT116 and in native human colon cancer tissues. We deorphanized the receptor and identified Troenan as an effective ligand. Troenan stimulation of HCT116 cells has anti-proliferative, anti-migratory and pro-apoptotic effects, mediated by changes in the intracellular calcium level upon PLC activation. These effects cause changes in the phosphorylation levels of p38, mTor and Akt kinases. Knockdown of the receptor via shRNA confirmed the involvement of OR51B4. This study emphasizes the importance of ectopically expressed ORs in the therapy for several diseases. The findings provide the basis for alternative treatments of colorectal cancer.